1997
DOI: 10.1099/00207713-47-3-713
|View full text |Cite
|
Sign up to set email alerts
|

Spiroplasma chrysopicola sp. nov., Spiroplasma gladiatoris sp. nov., Spiroplasma helicoides sp. nov., and Spiroplasma tabanidicola sp. nov., from Tabanid (Diptera: Tabanidae) Flies

Abstract: VOL. 47, 1997 FOUR NEW SPIROPLASMA SPECIES FROM TABANID FLIES 719 G. Wagner for assistance with isolation and culture and Mary Fenton for assistance with electron microarauhv.tales ord. nov.), with provision for familial rank to separate species with nonhelical morphology (Entomoplasmataceae fam. nov.) from helical species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The first indication that a newly isolated mollicute represents an Acholeplasma species often comes by finding that the organism is able to grow sustainably in serum-free media. However, apparent growth in serum-free media can be deceiving (Whitcomb, 1977;Whitcomb et al, 1997). Some mollicutes require very low levels of sterol for growth, which may be supplied in the passage volume when the cultures are passaged (Razin & Tully, 1970).…”
Section: (I) Culture Mediamentioning
confidence: 99%
“…The first indication that a newly isolated mollicute represents an Acholeplasma species often comes by finding that the organism is able to grow sustainably in serum-free media. However, apparent growth in serum-free media can be deceiving (Whitcomb, 1977;Whitcomb et al, 1997). Some mollicutes require very low levels of sterol for growth, which may be supplied in the passage volume when the cultures are passaged (Razin & Tully, 1970).…”
Section: (I) Culture Mediamentioning
confidence: 99%
“…definition of new groups and sub-groups (22) and required a complete revision of the group classification of spiroplasmas (28). Moreover, several other strains, including some isolated from France (13,14), remain to be fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of spiroplasmas have been isolated from horse flies and deer flies in both the USA (5-8, 11,[22][23][24][25] and France (4,9,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…In 1984, T. B. Clark and colleagues reported that tabanid flies (Diptera: Tabanidae) were a rich source of spiroplasmas (4). The strains reported in that paper and other strains discovered from tabanids since (9, 12,19,21,(24)(25)(26)(27)(28)30) represent 11 spiroplasma groups. One of these groups, group VIII, contains three subgroups (21,32).…”
mentioning
confidence: 99%